Communication Analysis Of Assistance Family Property Programs To Improve The Independence Of Beneficiary Families - Eceh Trisna Ayuh; Titi Darmi; Faizal Anwar (Kolaborasi : Jurnal Administrasi Publik, 2022)
The Family Hope Program (PKH) is community empowerment policy program from government. This study aims to know PKH facilitators communicate with KPM can be independent running their lives in the future. Research was conducted in several villages of Sukaraja sub-district, Seluma Regency, Bengkulu Province which get PKH mandate, research time was planned for 1 year. Data collection techniques through observation, in-depth interviews, FGD, internal seminars. Data analysis carried out by collecting data, condensing, presenting, verifying and making decisions. Based on research in the field, communication between facilitators and KPM, PKH in Sukaraja is running smoothly. P2K2 activities are carried out regularly once a month before corona virus. PKH facilitators should be patient with the various characteristics of KPM that are difficult to advise and motivate because of fact, KPM are poor people, where they are truly incapacitated both in financial and educational terms due to lack of knowledge and insight